Karakteristik Fisiko Kimia dan Sensoris Burger Kerang Darah (Anadara granosa) - Ervianti Ervianti; Herpandi Herpandi; Ace Baehaki (Universitas Sriwijaya, 2017)
The purpose of this research was to physical characteristics, chemical characteristics and sensory analysis burger blood clam. The Research was conducted in January until March 2017. This research used a randomized block design (RBD) consisted of one-factor treatment with two replications. Factor treatment consist of combinations blood clam and threadfin breams surimi 90% : 0%, 70% : 20%, 50% : 40%, 30% : 60%. The variables observed were chemical characteristics (moisture content, ash, protein, fat, and carbohydrate), physical characteristics (elasticity), and sensory analysis on appearance, flavor, texture, color and taste. Result of this research showed difference combinations blood clam and threadfin breams surimi had significantly effect on moisture content (68.15%, 69.85%, 70.84%, 71.14%), ash content (2.75%, 2.47%, 2.1%, 1.9%), protein content (14.72%, 15.43%, 18.18%, 19.44%) and fat content (5.38%, 3.78%, 2.51%, 1.6%) and elasticity (30.66 gf, 35.73 gf, 40.06 gf, 41.73 gf), The result of sensory analysis had significantly effect on appearance, texture, colour and flavor. The best treatment from the physical and sensory analysis was treatment A3 with combination blood clam and threadfin breams surimi 30% : 60%.